Evaluation of endothelial disorders in patients with ankylosing spondylitis in postcovid period - Rakhimova, M.B.; Akhmedov, Kh.S.; Khalmetova, F.I.; Sadikova, S.I. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Purpose of the study. To study the state of endothelial function in patients with ankylosing spondylitis who have undergone COVID-19 by assessing the flow-dependent vasodilation of the brachial artery and endothelin-1 in serum. The study involved 80 patients, of which 40 patients (average age 42,3±2,8 years) diagnosed with ankylosing spondyloarthritis who underwent COVID-19 (group I); 40 patients diag- nosed with ankylosing spondyloarthritis (average age 46,3±5,7 years, who did not tolerate COVID-19, 32 healthy volunteers (average age 30,3±6,8 years) made up the control group. Endothelin-1 in serum was determined by enzyme-linked immunosorbent assay; flow-dependent vasodilation of the brachial artery was determined using Philips Affinity 70 (Release 3,0.3, Philips Healthcare, USA). Results. Analysis of endothelin-1 levels showed statistically significant differences in this indicator be- tween healthy children and patients with groups I and II (0.213 [0.012; 0.368] and 0.227 [0.15; 0.315] pmol/L, respectively; p=0,027). Flow-dependent vasodilation of the brachial artery in healthy individuals was 9.82 [7.8; 11.2]%, in patients of groups I and II this indicator tended to decrease - 9.46 [6.5; 10.8]% and 9, 11 (p = 0, 026). Conclusion. A study of endothelial function in patients with ankylosing spondyloarthritis revealed an in- crease in nitric oxide concentration compared to that in healthy, probably compensatory, subjects. The flow-dependent vasodilation of the brachial artery and the endothelin-1 level did not significantly differ from similar parameters of the control group.